Wired and dangerous : how your customers have changed and what to do about it - Bell, Chip R. (BK business book., 2011)
In an era of economic stress, rapid change, and social networking, customers are distracted, disgruntled, and harder to please than ever. Picky, Fickle, Vocal, Wired, and Vain -- they have very little tolerance for error and are ready to spread the word quickly over the internet when things go wrong. If a company's customer service doesn't adapt to these new conditions, they will get burned by bloggers and viral videos that can severely damage their reputation. This book describes exactly what today's customers expect and how to give it to them.